2022
DOI: 10.3390/ijerph19116655
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening Program Delivered by Community Health Workers for Chinese Married Immigrant Women in Korea

Abstract: This quasi-experimental study used a cancer prevention program delivered by community health workers (CHWs) as an intervention to improve health literacy and increase screening uptake. The intervention group was educated by trained CHWs and received information about the nearby hospitals. After education, participants received telephone counseling once a month for 6 months. In the intervention group, CHWs met the participants individually and delivered the CD-ROM containing conversation scenarios with voice du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…In addition, this intervention also improved women's knowledge and attitudes regarding breast cancer. Our study is consistent with other studies suggesting that adequate educational programs can increase women's knowledge and attitudes about breast cancer [65][66][67]. Studies have suggested that women with adequate knowledge and positive attitudes are more likely to obtain screening and testing [68][69][70].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this intervention also improved women's knowledge and attitudes regarding breast cancer. Our study is consistent with other studies suggesting that adequate educational programs can increase women's knowledge and attitudes about breast cancer [65][66][67]. Studies have suggested that women with adequate knowledge and positive attitudes are more likely to obtain screening and testing [68][69][70].…”
Section: Discussionsupporting
confidence: 92%